2015
DOI: 10.1007/s00726-015-2104-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and membrane-disruption mechanism of charge-enriched AMPs exhibiting cell selectivity, high-salt resistance, and anti-biofilm properties

Abstract: Cationic antimicrobial peptides (AMPs) are essential components of the innate immune system, offering protection against invading pathogenic bacteria. In nature, AMPs serve as antibiotics with broad-spectrum antimicrobial and anti-biofilm properties. However, low effective stability in high-salt environments and physiological instability in biological membranes limit the applicability of naturally occurring AMPs as novel therapeutics. We therefore designed short synthetic cationic peptides by substituting key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…Cationic amino acids, such as lysine, play a key role in the interaction of AMPs with the negatively charged components of the bacterial cell surface and the cytoplasmic membrane (Shai, 1999; Hancock and Sahl, 2006). Therefore, an increase in peptide cationicity can promote a more efficient interaction with bacteria, and hence a stronger antibacterial activity (Han et al, 2016). Moreover, faster killing kinetics were observed for the analogs compared to TB against both S. aureus and P. aeruginosa , selected as representative Gram-positive and Gram-negative bacterial species, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Cationic amino acids, such as lysine, play a key role in the interaction of AMPs with the negatively charged components of the bacterial cell surface and the cytoplasmic membrane (Shai, 1999; Hancock and Sahl, 2006). Therefore, an increase in peptide cationicity can promote a more efficient interaction with bacteria, and hence a stronger antibacterial activity (Han et al, 2016). Moreover, faster killing kinetics were observed for the analogs compared to TB against both S. aureus and P. aeruginosa , selected as representative Gram-positive and Gram-negative bacterial species, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Salt resistance of pseudin-2 and its truncated analogs. Because the activities of some AMPs are known to be affected by the ionic strength of their environment, we investigated the effects of cations on the activities of the peptides (19). We found that in the presence of 300 mM Na ϩ , there was a slight reduction in the antibacterial activities of pseudin-2 and its truncated analogs against P. aeruginosa 4891 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the effect of the antibacterial peptide on biofilm formation, bacterial strains, including MDR strains (E. coli ATCC 25922 and CCARM 1238, S. aureus ATCC 25923 and CCARM 3090, and P. aeruginosa ATCC 27853 and 4891), were cultured in medium containing 0.2% glucose. Biofilm formation was then quantitatively analyzed as described previously (19). The MBIC was considered the lowest concentration that inhibited biofilm formation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations